2021
DOI: 10.1111/ans.17352
|View full text |Cite
|
Sign up to set email alerts
|

Utility of semi‐quantitative quick cortisol assay with low‐dose adrenocorticotropic hormone infusion adrenal vein sampling

Abstract: The corresponding author is not a recipient of a research scholarship.The paper is not based on a previous communication to a society or meeting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These procedures make patients uncomfortable, and moving between the same facility’s radiology suite and laboratory room increases the financial burden. Our new POCT-QCA enables us to perform ICM rapidly in a simple process with low costs and high success rates 16 , 18 , 19 . As the ICM reported previously, studies have revealed that our QCA improves radiation exposure during AVS and the success rate of AVS 20 .…”
Section: Discussionmentioning
confidence: 99%
“…These procedures make patients uncomfortable, and moving between the same facility’s radiology suite and laboratory room increases the financial burden. Our new POCT-QCA enables us to perform ICM rapidly in a simple process with low costs and high success rates 16 , 18 , 19 . As the ICM reported previously, studies have revealed that our QCA improves radiation exposure during AVS and the success rate of AVS 20 .…”
Section: Discussionmentioning
confidence: 99%